The Poetics of Secondary in the Coordinates of Confessional Modality of French Novel in the First Half of the XXth Century - Anastasia Stetsenko (Pitannâ Lìteraturoznavstva)
Ontological background of the twentieth-century contributed the conditions which made a French novel strive for the genre of confession. One of the main features which denotes the renewal of confessional poetics in French novel is the intensification of “secondary” elements semantics. The markers of the “secondary” within the coordinates of literary text are narrative techniques that carry the semantic load on the structural elements of the text, which are traditionally considered less important: words in brackets, parentheses, “superfluous” words or even the whole chapters etc. Therefore, due to these narrative techniques the “secondary” elements of a text (which previously could be read faster than the main text or even could be thrown out of it without loss for content) transform into the ideological core of a novel. The reasons of this phenomenon lie through examination both of the confession as a Christian Sacrament and the specialties of new external grounding which modified the poetics of confession in the twentieth century. The research focuses on the novels of French Catholic writers G. Bernanos, F. Mauriac, J. Green. The analysis of their novels allows explaining epistemological value of “secondary” elements in the twentieth-century art and clarifying the narrative strategies of modeling the confessional image of the twentieth-century French literature.